2010
DOI: 10.1632/prof.2010.2010.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Digital Scholarship: Exploring the Changing Realities of Intellectual Work

Abstract: Because published research is a significant component of tenure-andpromotion cases, even at institutions with an explicit teaching focus, faculty members often plan their pretenure scholarly activities on the basis of their understanding of how different types of scholarly work will be valued. At the same time, new technologies have influenced tenure-andpromotion considerations, expanding not only available venues of publication but also definitions of scholarly activity and production. Because these new techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Despite data showing increasing social media usage among the general public, many in academia view social media with distrust. Traditionally, peer pressure has discouraged scholars from communicating with the public via news media, as departments may perceive this as diminishing time for research and publications, negatively affecting academic careers, especially for tenure and promotion (Purdy & Walker, 2010; The Royal Society, 2006). Yet, patterns of U.S. scholars interacting with journalists have remained stable over the past three decades and are more frequent than often thought, depending on status, socialization, and intrinsic rewards for the scholar (Dunwoody, Brossard, & Dudo, 2009).…”
Section: Social Media Use By Scholarsmentioning
confidence: 99%
“…Despite data showing increasing social media usage among the general public, many in academia view social media with distrust. Traditionally, peer pressure has discouraged scholars from communicating with the public via news media, as departments may perceive this as diminishing time for research and publications, negatively affecting academic careers, especially for tenure and promotion (Purdy & Walker, 2010; The Royal Society, 2006). Yet, patterns of U.S. scholars interacting with journalists have remained stable over the past three decades and are more frequent than often thought, depending on status, socialization, and intrinsic rewards for the scholar (Dunwoody, Brossard, & Dudo, 2009).…”
Section: Social Media Use By Scholarsmentioning
confidence: 99%
“…More recently, Beattie [23] and Diamond [21] have advocated expanding the definition of scholarship to reflect practice in the twenty-first century. In the humanities, particularly English studies, for example, there has been a tendency to attempt to categorize digital outputs as equivalent to print publications instead of considering them in terms of "design and delivery, recentness and relevance, and authorship and accessibility" [24]. Activities, which are undertaken in so-called "nontraditional" areas, need to be recognized as well.…”
Section: The Changing Nature Of Scholarshipmentioning
confidence: 99%
“…While scholars have worked to categorize and theorize the scholarly activity happening on the web (Barton, 2005;Burton, 2009;Purdy & Walker, 2010;Warner, 2007), commenting features have received relatively little attention. In a study of digital scholarly work occurring in various online spaces including webtexts, blogs, Twitter, and discussion forums, James Purdy and Joyce Walker (2012) went so far as to code for "dialogic exchange," looking at when scholarly works encouraged and enacted direct or indirect dialogue, and they concluded that these spaces often served as a direct outlet to more formal scholarly productions because the ideas developed there found their way into other scholarship.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating this scholarly work for tenure and promotion is a documented challenge. Purdy and Walker (2010) contended, "Though we are beginning to recognize the importance of digital work, discussions have tended to focus primarily on establishing digital work as equivalent to print publications to make it count instead of considering how digital scholarship might transform knowledge-making practices" (p. 178). A year later, Anderson and McPherson (2011) made a similar argument that while there has been progress, tenure and promotion committees are "not now wellequipped" to evaluate multimedia scholarship (pp.…”
Section: Introductionmentioning
confidence: 99%